Edukasi Gizi dan Perubahan Berat Badan Remaja Overweight dan Obesitas - Simbolon, Demsa; Tafrieani, Windy; Dahrizal, Dahrizal (Politeknik Kesehatan Tanjungkarang, 2018)
The problem of overweight and obesity in various worlds is increasing rapidly. The national prevalence in Indonesia in an adolescent age group is 10.8% (8.3% obesity and 2.5% obesity) caused by inadequate knowledge of nutrition. This study aims to determine the effect of Nutrition Education on changes in body weight of overweight and obese adolescents in SMP Negeri 2 Kota Bengkulu. The type of research is quasi-experimental with pretest and posttest design with control group design. The sample of the study was 11-13 year old teenagers with 44 people using consecutive sampling technique and using Mann-Whitney test and Ancova test. The results showed changes in the mean body weight of adolescents before the intervention of 61.23 kg and the mean body weight of adolescents after being given 61.89 kg of education with the difference in body weight change is only 0.66 kg. There were no significant differences in mean changes in adolescent weight before and after Nutrition Education (p=0.307). Factors that affect Weight Change is pocket money (p=0.044). Parents are expected to manage pocket money so that children can minimize the purchase of snacks that can lead to obesity.